(untitled) (World Bulletin of Management and Law, 2023)
The article analyzes the features of the political system of Iran and the geopolitical situation at the beginning of the 21st century, its evolution under the influence of changes in the internal situation in the country and external factors that had a multidirectional effect on the processes of modernization. Contradictory trends within the political system and other vectors of the Iranian leadership’s strategy in the field of regional policy are being studied.